PENGARUH HARGA, PROMOSI PENJUALAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PT KEDAUNG MEDAN INDUSTRIAL - ., Faldy; ., Jefri; Simanjuntak, Demak Claudia Yosephine (2020)
This research was conducted at PT Kedaung Medan Industrial which is engaged in the production of household appliances such as glass, plates and so on. Decrease in purchasing decisions caused by price, sales promotion and product quality. Quantitative approach, the type of research is descriptive quantitative, and the nature of this research is descriptive explanatory. The method of data collection is done by interviews, questionnaires, and documentation. Data analysis method used is multiple regression. The population is 186 customers PT Kedaung Medan Industrial and sample is 110 customers. The calculation result of hypothesis testing partially obtained tcount> ttable or 2.908> 1.983 and significant obtained 0.004 <0.05, tcount> ttable or 2.789> 1.983 and significant obtained 0.006 <0.05, tcount> ttable or 2.071> 1,983 and significantly obtained 0.041 <0.05, means that partially Price, Sales Promotion and Product Quality has a positive and significant effect on the Purchasing Decision of PT Kedaung Medan Industrial. The results obtained calculated F count (11,479)> F table (2.69) and a significance probability of 0,000 <0.05, meaning that simultaneously Price, Sales Promotion and Product Quality has a positive and significant effect on the Purchasing Decision of PT Kedaung Medan Industrial. The coefficient of determination test results obtained Adjusted R Square value of 22.4% of the variation of the dependent variable is the purchase decision that can be explained by variations in the free variable price, sales promotion and product quality while the remaining 77.60% is explained by other variable.